Work Flexibility and Work-Life Balance: Gender and Workload Analysis - Chenny Chenny; Susanti Saragih (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
This study examines the role of work flexibility in enhancing employees' work-life balance. It specifically explores whether workload and gender serve as moderators of this relationship. The research is motivated by the growing prevalence of flexible work arrangements, particularly among Generation Z. The objective is to determine whether workload levels and gender affect the effectiveness of flexible work in supporting work-life balance. Quantitative design was employed in this study. Data was collected via an online questionnaire distributed to employees engaged in flexible working systems. A total of 180 respondents participated in the survey. Moderation analysis was conducted to assess both the direct effect of work flexibility on work-life balance and the moderating roles of workload and gender. The results show that work flexibility statistically has a significant effect on work-life balance. Furthermore, the interaction between workload and gender showed no significant effects. This indicates that the positive relationship between work flexibility and work-life balance is consistent across different levels of workload and gender. Thus, flexible work arrangements have universal benefits for enhancing employee well-being. The findings suggest important implications for organizations implementing flexible work systems. Managers are encouraged to adopt flexible work policies as a strategic means to support employee well-being, without requiring differentiation based on gender or workload. This is particularly relevant in managing the expectations and preferences of Generation Z employees. This study contributes to the literature by affirming the consistent positive impact of work flexibility on work-life balance, regardless of individual differences.